DIGITALLY DESIGNED PERIODONTAL PROTHESE SWING LOCK DENTURE : A CASE REPORT - Valentine Rosadi Sinaga (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Swing-lock framework partial removable denture is an option used as splinting in cases where there is several mobility teeth. The purpose of these periodontal prostheses was to help stabilize the teeth as adjuvant therapy. Swing-lock denture has more difficult construction and digital dentistry facilitates the fabrication process of swing-lock dentures by burn-out resin milling model making technique. Aim : This article was aimed to describe step by step how to make swing-lock partial denture with the help of digital design. Case report: a56 year old woman came to dental practice as she complained discomfort in old denture. In clinical condition it is found complete loss in upper jaw dan partial loss in low jaw with several mobility teeth. Complete denture was made in upper jaw and swing-lock partial denture in lower jaw using burn-out resin milling method that obtained through digital process. Conclusion: Swing-lock partial denture is a effective prostheses to achieve optimal function in difficult cases. Burn-out resin milling   technique facilitate the process of   fabricating   swing-lock denture